Recent advances in host-focused molecular tools for investigating host-gut microbiome interactions - Wang, Siyao; Gong, Xu; Xiao, Fei; Yang, Yun (Frontiers in Microbiology, 2024)
Microbial communities in the human gut play a significant role in regulating host gene expression, influencing a variety of biological processes. To understand the molecular mechanisms underlying host-microbe interactions, tools that can dissect signaling networks are required. In this review, we discuss recent advances in molecular tools used to study this interplay, with a focus on those that explore how the microbiome regulates host gene expression. These tools include CRISPR-based whole-body genetic tools for deciphering host-specific genes involved in the interaction process, Cre-loxP based tissue/cell-specific gene editing approaches, and in vitro models of host-derived organoids.Overall, the application of these molecular tools is revolutionizing our understanding of how host- microbiome interactions contribute to health and disease, paving the way for improved therapies and interventions that target microbial influences on the host.